Analytical methodologies for determination of methotrexate and its metabolites in pharmaceutical, biological and environmental samples - Forough Karami; Sara Ranjbar; Younes Ghasemi; Manica Negahdaripour (Elsevier, 2019)
Methotrexate (MTX) is a folate antagonist drug used for several diseases, such as cancers, various malignancies, rheumatoid arthritis (RA) and inflammatory bowel disease. Due to its structural features, including the presence of two carboxylic acid groups and its low native fluorescence, there are some challenges to develop analytical methods for its determination. MTX is metabolized to 7-hydroxymethotrexate (7-OH-MTX), 2,4-diamino-N10-methylpteroic acid (DAMPA), and the active MTX polyglutamates (MTXPGs) in the liver, intestine, and red blood cells (RBCs), respectively. Additionally, the drug has a narrow therapeutic range; hence, its therapeutic drug monitoring (TDM) is necessary to regulate the pharmacokinetics of the drug and to decrease the risk of toxicity. Due to environmental toxicity of MTX; its sensitive, fast and low cost determination in workplace environments is of great interest. A large number of methodologies including high performance liquid chromatography equipped with UV-visible, fluorescence, or electrochemical detection, liquid chromatography-mass spectroscopy, capillary electrophoresis, UV-visible spectrophotometry, and electrochemical methods have been developed for the quantitation of MTX and its metabolites in pharmaceutical, biological, and environmental samples. This paper will attempt to review several published methodologies and the instrumental conditions, which have been applied to measure MTX and its metabolites within the last decade. Keywords: Methotrexate, Antifolate, Anticancer, Quantification, High performance liquid chromatography